2008
DOI: 10.1016/j.immuni.2007.11.023
|View full text |Cite
|
Sign up to set email alerts
|

The Lupus-Related Lmb3 Locus Contains a Disease-Suppressing Coronin-1A Gene Mutation

Abstract: Here, we show that a lupus-suppressing locus is caused by a nonsense mutation of the filamentous actin-inhibiting Coronin-1A gene. This mutation was associated with developmental and functional alterations in T cells including reduced migration, survival, activation, and Ca2+ flux. T-dependent humoral responses were impaired, but no intrinsic B cell defects were detected. By transfer of T cells, it was shown that suppression of autoimmunity could be accounted for by the presence of the Coro1a(Lmb3) mutation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
118
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(123 citation statements)
references
References 48 publications
5
118
0
Order By: Relevance
“…Indeed, in the absence of coronin 1, MOG-specific T cell responses such as proliferation and cytokine expression after immunization with MOG peptide are delayed, as well as reduced, strongly suggesting a priming defect in the absence of coronin 1. In addition, several lines of evidence exclude a role for coronin 1 in Ag processing and presentation: 1) the restoration of EAE on transfer of wild-type T cells as shown in this study; 2) the absence of any defect in either macrophage, B cell, and dendritic cell function (3,24,25,38) and the absence of any gross defects in thymic selection, a process that is heavily dependent on Ag processing and presentation (19)(20)(21). Naive T cell priming, which is the initial step of an immune response, usually takes place in the draining lymph nodes where professional APCs activate naive T cells, leading to clonal expansion and differentiation into cytokine-expressing effector T cells.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Indeed, in the absence of coronin 1, MOG-specific T cell responses such as proliferation and cytokine expression after immunization with MOG peptide are delayed, as well as reduced, strongly suggesting a priming defect in the absence of coronin 1. In addition, several lines of evidence exclude a role for coronin 1 in Ag processing and presentation: 1) the restoration of EAE on transfer of wild-type T cells as shown in this study; 2) the absence of any defect in either macrophage, B cell, and dendritic cell function (3,24,25,38) and the absence of any gross defects in thymic selection, a process that is heavily dependent on Ag processing and presentation (19)(20)(21). Naive T cell priming, which is the initial step of an immune response, usually takes place in the draining lymph nodes where professional APCs activate naive T cells, leading to clonal expansion and differentiation into cytokine-expressing effector T cells.…”
Section: Discussionmentioning
confidence: 61%
“…Role for coronin 1 in the development of EAE Coronin 1 is a leukocyte-specific regulator of Ca 2+ -dependent signaling processes and is essential for the maintenance of the naive T cell pool in the periphery (19)(20)(21)(22). Despite diminished numbers of naive T cells (20), when coronin 1-deficient mice are immunized with a variety of Ags, normal Ab responses are generated (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronin 1A-deficient T cells exhibit reduced cytokine production, including of IL-2 and IFN-␥, and altered F-actin reorganization (29). Moreover, a nonsense mutation in coronin 1A was identified as a gene alteration associated with the Lmb3 locus, which plays a major role in modulating autoimmunity in Fas lpr mice (30).…”
mentioning
confidence: 99%
“…In mice deficient in the p57/coronin-1 gene, differentiation and chemokine-mediated trafficking of T cells were severely impaired (22,24,25). It was further demonstrated that the developments of experimental autoimmune encephalomyelitis (26,27) and lupus-like autoimmune disease (28) were suppressed in mice with genetic defects of p57/coronin-1. These studies suggested the potential relevance of p57/coronin-1 to allergic and autoimmune diseases.…”
mentioning
confidence: 99%